3 A NOVEL SOURCE OF REACTIVE OXYGEN SPECIES IN THE MITOCHONDRIA. Issue 1 (1st January 2007) - Block, K.; Gorin, Y.; Abboud, H. E.
Abstract : Oxidative stress has been implicated in diverse human diseases, including diabetes and atherosclerosis, as well as in aging. The bulk of oxidative pathways are harbored in the mitochondria, where various redox carriers leak electrons to oxygen to form superoxide anion. In phagocytic cells, however, gp91phox-based NAD(P)H oxidase has long been recognized as a major source of reactive oxygen species (ROS). More recently, several isoforms of gp91phox, called Nox proteins, have been cloned and identified in somatic cells. Nox4 was cloned from the kidney, and we have recently shown that it is a major source of ROS in renal cells and kidney tissue of diabetic animals. We generated specific rabbit polyclonal Nox4 antibodies and found that Nox4 localizes to mitochondria. Several approaches were used to confirm Nox4 localization. (1) Immunoblot analysis in cultured rat glomerular mesangial cells (MCs) as well as renal cortex revealed that Nox4 was present in crude mitochondrial fractions, in mitochondria-enriched heavy fractions and in purified mitochondria. (2) Independent confirmation of Nox4 localization to the mitochondria was analyzed by immunogold electron microscopy. (3) Immunofluorescence confocal microscopy was also used to localize Nox4 in MCs and nonrenal cells, such as aortic endothelial or vascular smooth muscle cells. Our observation was confirmed using the mitochondrial localization prediction program MitoProt, where the probability score for Nox4 obtained was identical to mitochondrial protein human cytochrome c oxidase subunit IV. Functionally, siRNA-mediated knockdown of Nox4 reduces NADPH oxidase activity in pure mitochondria and blocks glucose-induced mitochondrial superoxide generation. Our data provide the first evidence that a functional Nox4 is present and regulated in mitochondria, indicating the existence of a novel source of ROS in this organelle. Collectively, our findings offer a possible explanation for the data of the literature reporting that both mitochondria and Nox-containing oxidases are sources of ROS. The present demonstration that Nox4 resides in mitochondria and plays a key role in disease-induced oxidative stress may reconcile the mitochondrial and the NAD(P)H oxidase hypotheses.